Influence Of The Digital Economy On Sustainable Economic Development Of The Regions Of Uzbekistan - Bakhodirov, Akbarbek (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This paper investigates the transformative role of the digital economy in fostering sustainable economic development across the diverse regions of the Republic of Uzbekistan. Through an integrated analysis of digital infrastructure, public policy frameworks, and regional development indicators, the study assesses how digital technologies are influencing inclusivity, productivity, and ecological resilience. Employing a mixed-methods approach, the research synthesizes statistical data with strategic policy analysis, supported by region-specific case studies. Findings indicate that while digitalization has accelerated economic diversification and public service efficiency in urban centers, structural and institutional gaps continue to hinder similar progress in rural and peripheral regions. The paper concludes with evidence-based recommendations for balanced digital development, underscoring the imperative of equity-oriented policy design and localized innovation ecosystems.